An unusual presentation of foreign body rectum - Paruthy, Samir; Paruthy, Shivani B. (International Surgery Journal, 2021)
Retrieval of rectal foreign body (FB) is a surgical dilemma. Variables including FB size, shape, make, time of insertion, presentation in ER, associated injuries, local edema, contamination, reluctance to seek medical aid, multiple unsuccessful attempts for self-retrieval masked by improper history and concealing the actual facts makes surgical management challenging. In this study, two unusual cases of FB in rectum and retrievals were presented. Case 1 was a 22 year old boy with a metallic glass tumbler in rectum reported after 12 days with constipation and pelvic pain. Repeated self-attempts for removal by the patient further pushed the FB upwards. Retrieval of rectal FB was done from rectum with repair and diversion colostomy which was closed later. Patient confessed this was his thirteenth attempt with the same object with successful retrieval all the time in last nine months. Case 2 was a 27 year old boy who inserted a sharp iron rod (used for picking ice) in the anal region which migrated to sigmoid colon without perforation of the viscera. Patient reported after three days with sharp shooting pain in left lower abdomen which aggravated on defecation. Abdominal examination revealed no sign of peritonitis, X-ray and CECT abdomen unexpectedly revealed no viscera perforation. Retrieval of FB stuck at sigmoid colon was undertaken with repair and diversion colostomy and closed later. From the study it was concluded that the retrieval of FB with proper psychological evaluation along with rehabilitation of the patient in society was a multidisciplinary management. Actual algorithm of management of these cases was beyond the surgical clinics and one-time emergency FB retrievals.